Blockchain as a driver of innovation in the FinTech industry and modern financial markets - Dimic, Maja; Knezevic, Nikola; Arsenijevic, Olja (Industrija, 2025)
Abstract: This paper aims to analyze the role of blockchain technology in the transformation of the financial sector, with particular emphasis on its application within FinTech solutions and its potential to drive structural changes in financial markets. Over the past decade, FinTech has experienced rapid growth, significantly reshaping traditional financial services through digital innovation. This evolution is characterized by the integration of technologies that enable novel forms of access to financial products and services, including online banking, mobile payments, and digital lending platforms. Concurrently, there has been a pronounced increase in investment in technological innovations within the financial sector, reflecting a high level of market and institutional interest in FinTech solutions. Within this ongoing digital transformation, blockchain technology stands out as a disruptive infrastructure with the capacity to redefine operational, security, and regulatory frameworks of current financial systems. Its core attributes: decentralization, immutability of records, and transparency, facilitate accelerated transaction processing, reduction of transaction costs, elimination of intermediaries, and enhanced security of financial operations. Special attention in the analysis of modern FinTech innovations is given to smart contracts and decentralized finance (DeFi).